Epidemiologic characteristics and influencing factors of cluster infection of COVID-19 in Jiangsu Province. (10th February 2021) - Ai, Jing; Shi, Naiyang; Shi, Yingying; Xu, Ke; Dai, Qigang; Liu, Wendong; Chen, Liling; Wang, Junjun; Gao, Qiang; Ji, Hong; Wu, Ying; Huang, Haodi; et al.
Abstract: To understand the characteristics and influencing factors related to cluster infections in Jiangsu Province, China, we investigated case reports to explore transmission dynamics and influencing factors of scales of cluster infection. The effectiveness of interventions was assessed by changes in the time-dependent reproductive number ( Rt ). From 25th January to 29th February, Jiangsu Province reported a total of 134 clusters involving 617 cases. Household clusters accounted for 79.85% of the total. The time interval from onset to report of index cases was 8 days, which was longer than that of secondary cases (4 days) ( χ 2 = 22.763, P < 0.001) and had a relationship with the number of secondary cases (the correlation coefficient ( r ) = 0.193, P = 0.040). The average interval from onset to report was different between family cluster cases (4 days) and community cluster cases (7 days) ( χ 2 = 28.072, P < 0.001). The average time interval from onset to isolation of patients with secondary infection (5 days) was longer than that of patients without secondary infection (3 days) ( F = 9.761, P = 0.002). Asymptomatic patients and non-familial clusters had impacts on the size of the clusters. The average reduction in the Rt value in family clusters (26.00%, 0.26 ± 0.22) was lower than that in other clusters (37.00%, 0.37 ± 0.26) ( F = 4.400, P = 0.039). Early detection of asymptomatic patients and early reports of non-family clusters can effectively weaken cluster infections.